Enhanced inter-compartmental Ca2+ flux modulates mitochondrial metabolism and apoptotic threshold during aging - Corina T. Madreiter-Sokolowski; Markus Waldeck-Weiermair; Marie-Pierre Bourguignon; Nicole Villeneuve; Benjamin Gottschalk; Christiane Klec; Sarah Stryeck; Snjezana Radulovic; Warisara Parichatikanond; Saša Frank; Tobias Madl; Roland Malli; et al. (Redox Biology, 2019)
Background: Senescence is characterized by a gradual decline in cellular functions, including changes in energy homeostasis and decreased proliferation activity. As cellular power plants, contributors to signal transduction, sources of reactive oxygen species (ROS) and executors of programmed cell death, mitochondria are in a unique position to affect aging-associated processes of cellular decline. Notably, metabolic activation of mitochondria is tightly linked to Ca2+ due to the Ca2+ -dependency of several enzymes in the Krebs cycle, however, overload of mitochondria with Ca2+ triggers cell death pathways. Consequently, a machinery of proteins tightly controls mitochondrial Ca2+ homeostasis as well as the exchange of Ca2+ between the different cellular compartments, including Ca2+ flux between mitochondria and the endoplasmic reticulum (ER). Methods: In this study, we investigated age-related changes in mitochondrial Ca2+ homeostasis, mitochondrial-ER linkage and the activity of the main ROS production site, the mitochondrial respiration chain, in an in vitro aging model based on porcine aortic endothelial cells (PAECs), using high-resolution live cell imaging, proteomics and various molecular biological methods. Results: We describe that in aged endothelial cells, increased ER-mitochondrial Ca2+ crosstalk occurs due to enhanced ER-mitochondrial tethering. The close functional inter-organelle linkage increases mitochondrial Ca2+ uptake and thereby the activity of the mitochondrial respiration, but also makes senescent cells more vulnerable to mitochondrial Ca2+-overload-induced cell death. Moreover, we identified the senolytic properties of the polyphenol resveratrol, triggering cell death via mitochondrial Ca2+ overload exclusively in senescent cells. Conclusion: By unveiling aging-related changes in the inter-organelle tethering and Ca2+ communications we have advanced the understanding of endothelial aging and highlighted a potential basis to develop drugs specifically targeting senescent cells. Keywords: Mitochondria, Endoplasmic reticulum, Calcium signaling, ER-mitochondrial coupling, Vascular aging